Validity of Adult Learning Motivation Measurement Instruments: A Psychometric Analysis - Ahmad, Ahmad; Santos, Mariano Dos; Rashid, Salman (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
Learning motivation is an important factor in the success of adult education, both in non-formal programs, training, and community development. However, many existing motivation measurement instruments still come from formal education adaptation and have not gone through adequate psychometric tests. This study aims to analyze the validity of the instrument for measuring adult learning motivation. The method used was a quantitative survey involving 72 respondents aged 20-50 years from non-formal education and training programs in Central Lombok and West Lombok Regencies. The instrument consists of 25 statements with a five-point Likert scale. The validity of the content was tested using Aiken's V, while the validity of the construct was analyzed by Exploratory Factor Analysis (EFA) through the MSA test and Bartlett's Test using the R studio application. The results of the study showed that most of the items had medium to high category content validity. MSA values range from 0.64–0.88 and the Bartlett test yields χ² = 1369.036; df = 300; p < 0.001 which confirms the feasibility of the data. The EFA analysis found five factors with an eigenvalue of > 1, but four main factors were maintained with a total variance of 60.4%. These findings confirm that the instrument has adequate construct validity and can be used in adult education evaluation.